Variations in the Ionospheric Peak Altitude at Mars in Response to Dust Storms: 13 Years of Observations From the Mars Express Radar Sounder. Issue 5 (13th May 2020) - Girazian, Z.; Luppen, Z.; Morgan, D. D.; Chu, F.; Montabone, L.; Thiemann, E. M. B.; Gurnett, D. A.; Halekas, J.; Kopf, A. J.; Němec, F.
Abstract: Previous observations have shown that, during Martian dust storms, the peak of the ionosphere rises in altitude. Observational studies of this type, however, have been extremely limited. Using 13 years of ionospheric peak altitude data from the Mars Advanced Radar for Subsurface and Ionosphere Sounding instrument on Mars Express, we study how the peak altitude responded to dust storms during six different Mars years (MY). The peak altitude increased ∼10–15 km during all six events, which include a local dust storm (MY 33), three regional dust storms (MYs 27, 29, and 32), and two global dust storms (MYs 28 and 34). The peak altitude's orbit‐to‐orbit variability was exceptionally large at the apexes of the MY 29 and MY 32 dust seasons and dramatically increased during the MY 28 and MY 34 global dust storms. We conclude that dust storms significantly increase upper atmospheric variability, which suggests that they enhance dynamical processes that couple the lower and upper atmospheres, such as upward propagating gravity waves or atmospheric tides. Plain Language Summary: Limited observations have shown that dust storms at Mars significantly affect the upper atmosphere and ionosphere. In particular, the expansion of the atmosphere in response to solar heating of dust causes fixed pressure levels in the upper atmosphere to rise in altitude. The peak of the ionosphere–where the maximum electron density occurs–can be used as a diagnostic of this expansion because it forms at a fixed pressure level in the upper atmosphere (120–150 km). In this work, we use 13 years of observations from the radar sounder on the Mars Express spacecraft to evaluate how the peak altitude of the ionosphere varied during six different dust storms. We found that the peak altitude increased by 10–15 km during each dust storm. Additionally, the orbit‐to‐orbit variability of the peak altitude increased significantly during the dust storms, which suggests that dynamical processes that couple the lower and upper atmospheres were enhanced. Key Points: We show how the ionospheric peak altitude at Mars varies during six different dust storms The peak altitude rises 10–15 km during each dust storm Dust storms increase the peak altitude's variability, suggesting they enhance dynamical processes coupling the lower and upper atmospheres